2022
DOI: 10.1038/s41598-022-06933-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between prehospital fluid resuscitation with crystalloids and outcome of trauma patients in Asia by a cross-national multicenter cohort study

Abstract: Prehospital fluid resuscitation with crystalloids in patients following trauma remain controversial. This study aimed to investigate the association between prehospital fluid resuscitation and outcomes of trauma patients in Asia. We conducted a retrospective cohort study of trauma patients between 2016 and 2018 using data from the Pan-Asia Trauma Outcomes Study (PATOS) database. Prehospital fluid resuscitation was defined as any administration of intravenous crystalloid fluid on the ambulance before arrival to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Even though MRS was originally used for assessing stroke patients’ functional capability 20 , it has been applied to assess trauma patients 15 , 17 . We defined no symptoms, no significant disability, slight disability, and moderate disability (MRS 0–3) as favorable functional outcomes and moderately severe disability, severe disability, and death (MRS 4–6) as poor functional outcomes 15 17 , 21 , 22 . Additional analysis of the risk distribution was performed if a superior index was found.…”
Section: Methodsmentioning
confidence: 99%
“…Even though MRS was originally used for assessing stroke patients’ functional capability 20 , it has been applied to assess trauma patients 15 , 17 . We defined no symptoms, no significant disability, slight disability, and moderate disability (MRS 0–3) as favorable functional outcomes and moderately severe disability, severe disability, and death (MRS 4–6) as poor functional outcomes 15 17 , 21 , 22 . Additional analysis of the risk distribution was performed if a superior index was found.…”
Section: Methodsmentioning
confidence: 99%
“…These results are consistent with a seminal RCT by Bickell et al 17 who reported that adult trauma patients had worse outcomes if they received prehospital fluids compared with no fluids. A large cross-national report from Asia of more than 30,000 patients found an adjusted increased risk in death in adults who receive more crystalloids in the prehospital phase of resuscitation (adjusted odds ratio [AOR], 2.02; 95% CI, 1.32–3.10) 18 …”
Section: Crystalloidmentioning
confidence: 99%
“…A large cross-national report from Asia of more than 30,000 patients found an adjusted increased risk in death in adults who receive more crystalloids in the prehospital phase of resuscitation (adjusted odds ratio [AOR], 2.02; 95% CI, 1.32-3.10). 18…”
Section: Crystalloidmentioning
confidence: 99%
“…For traumatic injuries, the data is inconsistent and high quality evidence is lacking. Many clinical trials performed in a pre-hospital setting demonstrate that excessive fluid resuscitation improves outcomes ( 15 , 17 ), however, there are also studies that show the opposite result ( 16 , 37 ). However, in most cases the trials are inconclusive and do not support any type of treatment.…”
Section: Discussionmentioning
confidence: 99%